simplify the following:‐ (a‐b) (a²+b²+ab)‐(a+b) (a²+b²‐ab)?​

Question

simplify the following:‐ (a‐b) (a²+b²+ab)‐(a+b) (a²+b²‐ab)?​

in progress 0
Valentina 3 weeks 2021-11-07T10:35:41+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-11-07T10:37:12+00:00

    Answer:

    Step-by-step explanation:

    (b – a)/(a² – b²) = (b – a)/[(a – b)(a + b)]

    = [(-1)(a – b)]/[(a – b)(a + b)]


    By the Associative Property of Multiplication, i.e, for any numbers a, b, and c, a(bc) = (ab)c, we have:


    = [(a – b)/(a – b)][-1/(a + b)]


    = [1][-1/(a + b)]


    = -1/(a + b) is (b – a)/(a² – b²) simplified

    hope it helps

    🙂

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )